Control de la actividad administrativa y la tutela jurisdiccional efectiva - Ruocco, Graciela (Pontificia Universidad Católica del Perú, 2020)
La limitada extensión del presente estudio nos impide abordar el control de toda actividad administrativa, razón por la cual restringiremos el análisis a la actuación de la Administración en ejercicio del poder sancionatorio, y en particular a la valoración de la prueba producida y el ejercicio del derecho de defensa en sede administrativa, a la luz del principio de tutela jurisdiccional efectiva.

The limited extension of this study prevents us from addressing the control of any administrative activity, which is why we will restrict the analysis to the performance of the Administration in the exercise of the sanctioning power, and in particular to the assessment of the evidence produced and the exercise of the right of defense in administrative process, in the light of the principle of effective jurisdictional protection.
Control of the administrative activity and effective jurisdictional protection
Keywords: Control jurisdiccional; Tutela jurisdiccional efectiva; Prueba; Actos sancionatorios; https://purl.org/pe-repo/ocde/ford#5.05.00